MOBILE APPLICATIONS FOR FACILITIES MANAGEMENT INFORMATION - Zainal, Nurul Natrah; Ahmad, Faridahanim; Hanipah, Mohd Hafizal; Musa, Mohd Kamaruzaman; Awang, Mariah; Abdul Rahman, Mohammad Ashraf; Abidin, Nur Izie Adiana; Hamidon, Nuramidah; Mohamed Yusop, Fatimah; Adnan, Suraya Hani; Ahmad, Suhaida; Ishak, Shahrul Azhan; et al. (Innovare Academics Sciences PVT. LTD, 2020)
People are becoming more dependent on mobile phones to conduct everyday routine activities such as reading, shopping, and learning, as well as complaining. More innovative design mobile applications have been created by mobile application developers. The increment of complaints from a citizen regarding public facilities problem causes the lack of strategic communication between authorities and citizens. Therefore, this study aims to evaluate the usability of existing mobile applications that are being used by the government, namely, i-Tegur and e-Taman, for better communication performance between authorities and citizens. The usability elements, learnability and ease of use, and the features between i-Tegur and e-Taman, were compared. Other usability elements are proposed for evaluating the usability of mobile applications for complaints relating to facilities management and for developing new mobile applications with excellent usability. The usability of mobile applications evaluated by the System Usability Scale (SUS) Questionnaire and the usability score calculated by using SUS Application. Results indicate both mobile applications have slightly different usability score but still in an acceptable usability range. Both mobile applications have high learnability and are easy to use. Furthermore, e-Taman has more advantageous features than i-Tegur. In a future, facilities management complaints need to upgrading from time to time.